From "Physical Displacement" to "Meaning Construction": The Transformation Path of Localized Educational Research Resources——A Case Study of Qiqihar’s "Five-Colored Education" Resources - Ying Ren; Dan Yao (Education Research on Study Tours and Practice, 2026)
As study-travel practice education gains broader adoption, it commonly faces superficial challenges such as "travel without learning" and "superficial, cursory engagement." This paper examines local resources in Qiqihar as a research framework, exploring pathways for deepening the transformation of study-travel practices from spatial displacement ("going out") to meaningful context-building ("taking root"). Grounded in situated learning and embodied cognition theories, the study deciphers the unique educational significance of Qiqihar’s "natural-cultural-industrial" resources. Leveraging Heilongjiang Province’s "Five-Colored Education" framework and the "Three-Stages-Nine-Steps" model, it establishes a cross-grade project-based curriculum system linked through a "story chain." Additionally, the study proposes reconstructing performance evaluation using a "growth evidence portfolio" and emphasizes teachers’ professional development and identity transformation as "curriculum designers," aiming to provide theoretical references and practical models for deeply integrating educational value with local context in regional study-travel practices.